IMPROVING LEARNERS' ENGLISH WRITING SKILLS THROUGH DIGITAL TECHNOLOGY AND PROJECT-BASED LEARNING - Suryani, Nyayu Yayu; Rizal, Syamsul; Rohani, Tri; Ratnaningsih, Herin (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
This groundbreaking research endeavors to elevate participants' learning competence through the innovative integration of digital technology as a pedagogical medium. Pioneering a novel approach, this study seeks to gauge the efficacy of digital-based technology in enhancing English writing proficiency and participants' perceptions of its utility on the Storyboard That platform. Adopting a quantitative methodology, data is meticulously collected from experimental and control groups comprising nursing participants. Leveraging a synergistic blend of digital technology and project-based learning (PjBL), the research yields noteworthy gains in both knowledge and attitudes, with N-gain scores of 0.53 and 0.52, respectively. While initial trial results place competence and integration in the medium category, there exists a compelling imperative for further refinement and enhancement. The findings underscore the transformative potential of digital technology in augmenting writing skills and platform utilization, laying the groundwork for future innovations in English language education. By advocating for the seamless integration of digital tools like Storyboard That into the curriculum, this research not only fosters creativity and proficiency in English writing but also cultivates a dynamic learning environment conducive to holistic skill development. Ultimately, this study serves as a clarion call for educators to embrace the transformative power of digital technology in fostering English language proficiency and nurturing a generation of digitally literate and proficient learners poised to thrive in an increasingly interconnected world.